Promotion of direct electron transfer between Shewanella putrefaciens CN32 and carbon fiber electrodes via in situ growth of α-Fe2O3 nanoarray - He, Xiu; Lu, Hao; Fu, Jingjing; Zhou, Huang; Qian, Xingchan; Qiao, Yan (Frontiers in Microbiology, 2024)
The iron transport system plays a crucial role in the extracellular electron transfer process of Shewanella sp. In this study, we fabricated a vertically oriented α-Fe2O3 nanoarray on carbon cloth to enhance interfacial electron transfer in Shewanella putrefaciens CN32 microbial fuel cells. The incorporation of the α-Fe2O3 nanoarray not only resulted in a slight increase in flavin content but also significantly enhanced biofilm loading, leading to an eight-fold higher maximum power density compared to plain carbon cloth. Through expression level analyses of electron transfer-related genes in the outer membrane and core genes in the iron transport system, we propose that the α-Fe2O3 nanoarray can serve as an electron mediator, facilitating direct electron transfer between the bacteria and electrodes. This finding provides important insights into the potential application of iron-containing oxide electrodes in the design of microbial fuel cells and other bioelectrochemical systems, highlighting the role of α-Fe2O3 in promoting direct electron transfer.